ANALYSIS AND DESIGN OF 250 WATTS BRUSHLESS DC MOTORS FOR URBAN ELECTRIC BICYCLES - Zalfa Aliyadin, Adzhani
ANALYSIS AND DESIGN OF 250 WATTS BRUSHLESS DC MOTORS FOR URBAN ELECTRIC BICYCLES Adzhani Zalfa Aliyadin ABSTRACT Electric bicycles have become one of the most popular vehicle modes in recent years. With that, comes a need of a research regarding BLDC motors, as one of the main components in a electric bicycle, in order to get the optimal design for its use in electric bicycles. In this final project, research is carried out focusing on the winding design of a BLDC motor for electric bicycles. Using a Bafang BLDC hub motor as a reference motor, which has a 18 slot-20 pole configurations, a reverse-engineering process is carried out to obtain a more optimal design. An analysis is done related to the effect of each winding parameter on motor performance. Based on this analysis and the criteria for e-bike BLDC, three winding design option is proposed. The design criteria for electric bicycles BLDC are determined from the needs of the rider, government regulations, and physical limitations. The winding design that fulfill the criteria and is the easiest to be implemented is chosen. The proposed design is compared with the reference design in regard to its performance. Finally, an analysis of the magnetic flux distribution was carried out for the proposed design. Based on the experiment, it was found that the proposed design has better performance than the reference design. It was found that the proposed design has the ability to generate 250 watts of constant power for a wider speed range, and has higher efficiency. Keywords—BLDC, electric bicycles, winding design, FEM analysis